The Influence of The Higgs Domino Online Game on The Learning Outcomes of Students - Resvi, Andi; Zulfikar Marsiding; Taswin, Dwi Pratiwi (IJESS International Journal of Education and Social Science, 2023)
This study aims to determine the effect of the Higgs Domino Online Game on Student Learning Outcomes at SMAN 10 Jeneponto. The population in this study were 127 students. The research subjects were 96 students of class XII at SMAN 10 Jeneponto, using the simple random sampling technique with the Slovin formula. The research method is quantitative, data was collected using a questionnaire compiled with a Likert scale for each variable, namely the higgs domino online game scale and learning outcomes were tested for validity and reliability. Test the hypothesis with simple regression that has gone through the classic assumption test. Obtained a significance level (P) of 0.000 (p <0.05). This shows that there is a significant influence between the Higgs Domino online game on student learning outcomes at SMAN 10 Jeneponto. Then based on the value of R Square (R^2) it can be said that 34.8% of the variation in learning outcomes obtained is explained by the higgs domino online game of 34.8% in this study.